2021
DOI: 10.3389/fphys.2021.698209
|View full text |Cite
|
Sign up to set email alerts
|

Vasoconstriction Response to Mental Stress in Sickle Cell Disease: The Role of the Cardiac and Vascular Baroreflexes

Abstract: Recent studies have shown that individuals with sickle cell disease (SCD) exhibit greater vasoconstriction responses to physical autonomic stressors, such as heat pain and cold pain than normal individuals, but this is not the case for mental stress (MTS). We sought to determine whether this anomalous finding for MTS is related to inter-group differences in baseline cardiac and vascular autonomic function. Fifteen subjects with SCD and 15 healthy volunteers participated in three MTS tasks: N-back, Stroop, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…7,15 Many cardiovascular adaptations of pregnancy are mediated by vascular signalling changes. 16,17 People with SCD have well described vascular damage and aberrant vascular responsiveness 18,19 which may limit their physiological adaptations to pregnancy. Previous studies have demonstrated abnormally low prostaglandin to thromboxane ratios during pregnancy in people with HbSS compared to unaffected pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…7,15 Many cardiovascular adaptations of pregnancy are mediated by vascular signalling changes. 16,17 People with SCD have well described vascular damage and aberrant vascular responsiveness 18,19 which may limit their physiological adaptations to pregnancy. Previous studies have demonstrated abnormally low prostaglandin to thromboxane ratios during pregnancy in people with HbSS compared to unaffected pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of VOCs varies widely across SCD individuals with a recent systematic review reporting a range of 0–18 per year 2 . Recent studies suggest that the occurrence of VOCs is associated with abnormal vasoconstriction patterns resulting from dysfunction of the autonomic nervous system, endothelial dysfunction, and/or psychological stress 3 5 . Central nervous system (CNS) factors may also contribute to VOCs.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of VOCs varies widely across SCD individuals with a recent systematic review reporting a range of 0 to 18 per year [48]. Recent studies suggest that the occurrence of VOCs is associated with abnormal vasoconstriction patterns resulting from dysfunction of the autonomic nervous system, endothelial dysfunction, and/or psychological stress [8,40,43]. Central nervous system (CNS) factors may also contribute to VOCs.…”
Section: Introductionmentioning
confidence: 99%